Teaching Legislative Politics Through a Game: Active Learning, Assignment Co-creation, and Assessment Across Modalities - Clemens, Jennifer L.; Hansen, Michael A. (Taylor and Francis Group, 2026)
This study examines the use of a legislative politics simulation game as a tool to engage students in advanced political science courses and provide an experiential learning environment. Designed to simulate the legislative process, the game allows students to propose the structure of their final assessments, which fosters critical thinking, collaboration, and co-creation. This study contributes in three ways: it demonstrates the use of a simulation game as an active learning tool in legislative politics, highlights the role of student co-creation in shaping assessments, and evaluates the effectiveness of simulations across different instructional modalities. The game was tested across five semesters, employing face-to-face, hybrid, and fully online formats. Course evaluations highlighted the game’s success in increasing belief that course activities matched learning objectives. However, while the game proved to be an effective pedagogical tool in face-to-face and hybrid settings, challenges emerged in online iterations, particularly regarding student participation and engagement. This study underscores the importance of adapting simulations to different instructional environments and offers insights into the limitations of fully asynchronous formats. The findings suggest that while simulations can enhance learning in legislative politics courses, their success is context dependent.